2019
DOI: 10.1159/000499177
|View full text |Cite
|
Sign up to set email alerts
|

Brain Connectivity in Ateles geoffroyi: Resting-State Functional Magnetic Resonance Imaging of Working Memory and Executive Control

Abstract: The objective of this research was to describe the organization and connectivity of the working memory (WM) and executive control (EC) networks in Ateles geoffroyi in resting-state conditions. Recent studies have shown that resting-state activity may underlie rudimentary brain functioning, showing that several brain regions can be tonically active at rest, maximizing the efficiency of information transfer while preserving a low physical connection cost. Whole-brain resting-state images were acquired from three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 96 publications
(203 reference statements)
0
3
0
1
Order By: Relevance
“…Functionally connected brain structures that are more active during rest than during tasks that require attention to external events comprise the DMN [ 67 , 74 , 75 ]. Recent studies have suggested that resting-state activity, which maximizes the efficiency of information transfer with low physical connection costs, can serve as the foundation for underlying brain functions [ 76 ]. Increasing evidence has shown that the resting state EEG rhythms may reveal abnormalities of the basic neurophysiological mechanisms that underlie cognition in AD subjects, and these abnormal EEG rhythms are thought to be associated with functional cortical disconnections [ 77 ].…”
Section: Introductionmentioning
confidence: 99%
“…Functionally connected brain structures that are more active during rest than during tasks that require attention to external events comprise the DMN [ 67 , 74 , 75 ]. Recent studies have suggested that resting-state activity, which maximizes the efficiency of information transfer with low physical connection costs, can serve as the foundation for underlying brain functions [ 76 ]. Increasing evidence has shown that the resting state EEG rhythms may reveal abnormalities of the basic neurophysiological mechanisms that underlie cognition in AD subjects, and these abnormal EEG rhythms are thought to be associated with functional cortical disconnections [ 77 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using MRIs in a resting state with spider monkeys, some authors have identified a memory network that includes the prefrontal cortex, temporal lobes, and the hippocampus (Platas-Neri et al, 2019), which are areas that have been related to executive functions previously (Chudasama, 2011;Robbins, 2000); spatial cognition (Hartley et al, 2014;Herweg & Kahana, 2018) and memory (Eichenbaum, 2007;Templer & Hampton, 2013), opening future possibilities of using neural field activity to predict the behavior of spider monkeys using the DFT.…”
Section: Discussionmentioning
confidence: 99%
“…Tuvimos la oportunidad de colaborar con el equipo dirigido por la Dra. Diana Platas Neri (Platas-Neri et al, 2019) en el análisis de la co-nectividad cerebral en primates no humanos (Ateles geoffroyi), mediante el análisis de las redes en estado de reposo asociadas a la memoria de trabajo y al control ejecutivo, así como la comparación de las activaciones (resonancia magnética funcional) obtenidas en humanos y otros primates. Uno de los principales resultados fue que las activaciones fueron similares a las encontradas en humanos en la porción basal prefrontal y en el área frontopolar.…”
Section: Desarrollounclassified